Genetic Variation at the LDL Receptor and HMG CoA Reductase Gene Loci, Lipid Levels, Statin Response, and Cardiovascular Disease Incidence in PROSPER - Polisecki, Eliana (Atherosclerosis, 2008)
Our purpose was to evaluate associations of single nucleotide polymorphisms (SNPs) at the low density lipoprotein (LDL) receptor (LDLR C44857T, minor allele frequency (MAF) 0.26, and A44964G, MAF 0.25, both in the untranslated region) and HMG-CoA reductase (HMGCR i18T>G, MAF 0.019) gene loci with baseline lipid values, statin induced LDL- cholesterol (C) lowering response, and incident coronary heart disease (CHD) and cardiovascular disease on trial (CVD). Our population consisted of 5804 elderly men and women with vascular disease or one or more vascular disease risk factors, who were randomly allocated to pravastatin or placebo. Other risk factors and apolipoprotein (apo) E phenotype were controlled for in the analysis. Despite a prior report, no relationships with the HMGCR SNP were noted. For the LDLR SNPs C44857T and A44964G we noted significant associations of the rare alleles with baseline LDL-C and triglyceride levels, a modest association of the C44857T with LDL-C lowering to pravastatin in men, and significant associations with incident CHD and CVD of both SNPs, especially in men on pravastatin. Our data indicate that genetic variation at the LDLR locus can affect baseline lipids, response to pravastatin, and CVD risk in subjects placed on statin treatment.